2011
DOI: 10.1111/j.1365-2362.2010.02445.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum MMP 2 and TIMP 2 in patients with inguinal hernias

Abstract: The patients with inguinal hernia have a statistically significant increase in serum levels of MMP-2. Our finding of the MMP-2 and TIMP-2 distinctly higher in the patients suffering from recurrence of direct inguinal hernia (reflecting a previous surgical failure) may suggest the theory that the extracellular matrix defect lies at the basis of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
(40 reference statements)
0
24
0
Order By: Relevance
“…It should be stressed that the assays measured the levels of the active form of MMP-2. Contemporary studies have revealed a correlation between the activity of MMP-2 in tissues and its blood level in patients with hernias, where it is significantly -compared with the control group -higher regardless of the patients' age, with much higher enzyme levels observed in younger patients with simple inguinal hernias (11,12,15,16,17). The blood level of MMP-2 and TIMP-2 in patients with inguinal hernias was also tested, with the results showing -as in the studies mentioned earlier -a significantly higher blood level of MMP-2 in those patients compared with the control group and a significantly higher blood level of MMP-2 and TIMP-2 in the patients with recurrent inguinal hernia, leading to the conclusion that metabolic disorders of extracellular matrix is the underlying cause of recurrent hernias (17).…”
Section: Discussionmentioning
confidence: 97%
“…It should be stressed that the assays measured the levels of the active form of MMP-2. Contemporary studies have revealed a correlation between the activity of MMP-2 in tissues and its blood level in patients with hernias, where it is significantly -compared with the control group -higher regardless of the patients' age, with much higher enzyme levels observed in younger patients with simple inguinal hernias (11,12,15,16,17). The blood level of MMP-2 and TIMP-2 in patients with inguinal hernias was also tested, with the results showing -as in the studies mentioned earlier -a significantly higher blood level of MMP-2 in those patients compared with the control group and a significantly higher blood level of MMP-2 and TIMP-2 in the patients with recurrent inguinal hernia, leading to the conclusion that metabolic disorders of extracellular matrix is the underlying cause of recurrent hernias (17).…”
Section: Discussionmentioning
confidence: 97%
“…In recent researches, an increase in MMPs (MMP: 1, 2, 9) was found to play a role in IH aetiopathogenesis. 17,18 In preterms with RDS, high levels of MMP-2 and MMP-9 are formed. 19,20 The high levels of MMPs might cause IH development by damaging the structure of immature inguinal canal.…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of altered collagen ratio in the presence of recurrence confirms the assumption of a basic problem of wound healing as reason for recurrences, rather than just being the result of technical failures. 7,17,18 Interestingly, this was found even more often with class 1 meshes (83 vs. 64%) and may indicate either that at least the two class 1 devices did not improve the local quality of collagens at the interface to the mesh, or that patients with normal collagen I to III ratio more often develop a recurrence (for technical reasons) if they received a class 2 meshes, or simply that class 1 meshes are used more often in patients with high risk for recurrence.…”
Section: Discussionmentioning
confidence: 99%